2019
DOI: 10.1159/000492829
|View full text |Cite
|
Sign up to set email alerts
|

Second Trimester Biochemical Markers as Possible Predictors of Pathological Placentation: A Retrospective Case-Control Study

Abstract: <b><i>Objective:</i></b> We aimed to evaluate the association between second trimester biochemical markers and pathological placentation. <b><i>Methods:</i></b> This was a retrospective case-control study (2007–2014) of singleton gestations at a university-affiliated tertiary center. Women with pathologic placentation were subdivided into three groups: placenta accreta (group A), placenta previa (group B), or both (group C). We compared second trimester biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…In recent years, researchers have focused on the discovery of biochemical markers that can help diagnose AIP during the antenatal period. It has been claimed that an increase in cell-free β-hCG mRNA in maternal serum and the presence of β-hCG and AFP in the second trimester can predict AIP [26,27]. Jing et al emphasized that increased human placental lactogen mRNA levels in maternal plasma may predict AIP, but they noted that it could not determine whether hysterectomy would be required [28].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have focused on the discovery of biochemical markers that can help diagnose AIP during the antenatal period. It has been claimed that an increase in cell-free β-hCG mRNA in maternal serum and the presence of β-hCG and AFP in the second trimester can predict AIP [26,27]. Jing et al emphasized that increased human placental lactogen mRNA levels in maternal plasma may predict AIP, but they noted that it could not determine whether hysterectomy would be required [28].…”
Section: Discussionmentioning
confidence: 99%
“…25 Both AFP and hCG in the second trimester was also associated with pathologic placentation. 29 Elevated inhibin A, which is secreted from the corpus luteum and feto-placental unit, 30 is also associated with accelerated differentiation of cytotrophoblast and alterations of syncytiotrophoblast morphology, 31 being a marker of placental oxidative stress. 32…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of biological markers, such as hCG in maternal serum are thought to result from early placental vascular damage and possibly be due to their greater absorption into maternal blood ow 11 . Berezowsky et al found that second trimester hCG levels were signi cantly higher among cases of pathological placentation, such as those in the spectrum of placenta previa and placenta accreta 12 . Interestingly, we found higher levels of hCG the longer the LLP persisted.…”
Section: Discussionmentioning
confidence: 99%